Morphological, technological and biopharmaceutical studies of alginate-chitosan microcapsules with vinpocetine - Yu. A. Polkovnikova; N. A. Severinova; K. N. Koryanova; U. A. Tulskaya; M. V. Grechkina (Фармация и фармакология (Пятигорск))
The aim of the investigation is to study morphological, technological and biopharmaceutical properties of alginate-chitosan microcapsules with Vinpocetine.Materials and Methods: Alginate-chitosan microcapsules with different concentrations of sodium alginate (0.5%, 1%, 1.5%, 2%, 2.5% and 3%) and a medium viscosity chitosan solution (0.25-0,5%), as well as microcapsules not treated with a solution of chitosan, were obtained. The surface morphology was studied by methods of atomic-powered microscopy with the use of an NT-MDT Corporation probe scanning microscope (model Solver P47 Pro). To study biopharmaceutical properties of the obtained microcapsules, the "Rotating Basket" apparatus was used.Results: It has been found out that the microcapsules not treated with a chitosan solution, have a smooth, transversely striated surface with large heights and deep cavities. With an increase in the concentration of sodium alginate, the surface becomes smoother, the peaks become larger, higher and wider, the cavities get deeper and more sinuous. The microcapsules treated with a chitosan solution, on the contrary, have a rough surface, low heights and shallow cavities, and with an increase in the concentration of sodium alginate, the surface becomes rougher, the heights are evenly distributed along the microcapsule. The spectrophotometry method was used to determine the efficiency of microencapsulation and the release rate of Vinpocetine from the microcapsules per unit time. When the concentration of a sodium alginate solution is 2.5%, the efficiency of microencapsulation is maximum (86.8%). At this concentration, saturation occurs and with its further increase, the efficiency decreases. The maximum release rate of Vinpocetine from microcapsule samples is observed when the concentration of a sodium alginate solution is 1%: it amounts to 41.17%.Conclusion. The amplitude parameters of the microcapsules surface are different at different concentrations. There is a pattern of alternating signs of asymmetry and excess in the samples with chitosan. With a change in the scale of scanning, the surface characteristics of the microcapsules change. The most distinctive details of the structure are visible at the scale of 2 x 2 pm2. At the concentration of sodium alginate of 2.5%, the efficiency of microencapsulation is maximum (86.8%). Studying the effect of the concentration of a sodium alginate solution on the release rate of Vinpocetine from the microcapsule samples has shown that at the concentration of 1%, the release rate is 41.17%, and at the concentration of 2.5% it is 4.5%. These microcapsules can be used in order to produce capsules with modified release.